Pengembangan bahan ajar SBdP bidang musik berbasis pendekatan saintifik untuk SD kelas V - Adib Wahyu Setiawan; Karsono Karsono; Joko Daryanto (Universitas Sebelas Maret, 2019)
Abstract. The purposes of this research were: 1) to describe the teacher's need about music (SBdP) teaching material based on scientific approach for the 5th grade of elementary school student; 2) to develop the initial design of music (SBdP) teaching materials based on scientific approach for the 5th grade of elementary school student; and 3) to explain the form of a music (SBdP) teaching material based on scientific approach prototype (initial draft) for the 5th grade of elementary school student. The research method that used in this research was Research & Development (R & D). This research method consisted of two stages, that were Stage I (preliminary studies) and stage II (development). The preliminary studies stage was carried out in eight elementary schools in the Laweyan district Surakarta by using some technique which were questionnaire, interviews and document analysis. After getting data from the preliminary studies, then the data would process by using qualitative descriptive analysis. The development stage consisted of product design preparation, product design validation and product testing. The results of this research explained that there was a teacher’s need to develop music (SBdP) teaching materials. Teaching material was a companion that could help teachers to optimize music learning. The product that had developed was music (SBdP) teaching materials based on the scientific approach. The design of this product (teaching material prototype) got a very good assessment from the expert. The results of limited trials showed that tcount<ttable (1,71791 < 1,7291) which means it was at the 95% confidence level, and the average of the student’s test score that had used music (SBdP) teaching materials based on the scientific approach was not equal to 75.Keywords: Teaching material, SBdP, scientific approach, elementary school